2020
DOI: 10.3233/jad-190997
|View full text |Cite
|
Sign up to set email alerts
|

β-Lactolin, a Whey-Derived Lacto-Tetrapeptide, Prevents Alzheimer’s Disease Pathologies and Cognitive Decline

Abstract: The prevention of age-related memory decline and dementia has been becoming a high priority because of the rapid growth in aging populations. Accumulating epidemiological and clinical studies indicate that intake of fermented dairy products rich in ␤-lactolin improves memory retrieval and executive function and attenuates cognitive decline in the elderly. However, the effects of long-term consumption of ␤-lactolin on Alzheimer's disease (AD) pathologies have not been investigated. In the present study, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Treatment with the dopamine D1 receptor antagonist attenuates the memory improvement by of β-lactolin in amnesia model mice. In addition, our previous preclinical studies had shown that the levels of dopamine in the cortex were reduced in a 5×FAD mice model of Alzheimer’s disease [ 13 , 53 ]. The aforementioned reports therefore suggest that β-lactolin improves the dopaminergic system and increases CBF within the DLPFC, promoting improvements in cognitive decline and dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with the dopamine D1 receptor antagonist attenuates the memory improvement by of β-lactolin in amnesia model mice. In addition, our previous preclinical studies had shown that the levels of dopamine in the cortex were reduced in a 5×FAD mice model of Alzheimer’s disease [ 13 , 53 ]. The aforementioned reports therefore suggest that β-lactolin improves the dopaminergic system and increases CBF within the DLPFC, promoting improvements in cognitive decline and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Orally administered β-lactolin is delivered to the brain, where it inhibits monoamine oxidase B (MAO-B) activity in mice, subsequently increasing the levels of dopamine in the cortex and hippocampus [ 11 , 12 ]. β-Lactolin has been found to improve spatial working memory and episodic object recognition memory in mice and aged mice with pharmacologically induced amnesia [ 6 ], as well as improve cognitive decline and suppress Alzheimer’s pathologies, including inflammation and Aβ deposition in the brain of transgenic 5× FAD mice with Alzheimer’s disease [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported reduced dopamine levels in the cortex region of 5×FAD mice, a model for Alzheimer’s disease. β-lactolin treatment increased dopamine levels, reduced amyloid-β levels, and improved memory impairment [ 9 ]. Moreover, supplementation with β-lactolin improved memory retrieval and attention associated with dorsolateral frontal cortex function in older healthy adults [ 10, 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…β-lactolin increases monoamine levels in the cortex and hippocampus regions; moreover, it has been shown to improve spatial working memory and attention in mice with pharmacologically induced amnesia [ 7, 8 ]. β-lactolin has also been shown to suppress memory impairment and Alzheimer’s disease pathology in an Alzheimer’s disease transgenic mouse model [ 9 ]. We previously reported that supplementation with β-lactolin-rich whey peptides for 6 weeks improved the scores of the verbal fluency test (VFT), which evaluates the executive function and memory retrieval, and the Stroop test, which evaluates inhibition of attention, in healthy middle-aged adults compared to those in the placebo group [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…BDNF-TrkB signaling pathway has been reported to play a key role in learning and memory (Boulle, Kenis et al 2012). The expression level of BDNF is significantly decreased in the hippocampus of 3-m old 5×FAD mice (Ano, Ohya et al 2020). R13 is a prodrug of 7,8-DHF, which stably exists in an acidic environment.…”
Section: Discussionmentioning
confidence: 99%